Muscle growth affects the metabolome of the pectoralis major muscle in red-winged tinamou (Rhynchotus rufescens) - de Moraes Vilar, Claudianny Souto Maior; Malheiros, Jessica Moraes; da Silva, Pollyana Ferreira; Martins, Eduardo Henrique [UNESP]; dos Santos Correia, Luiz Eduardo Cruz [UNESP]; de Oliveira, Matheus Henrique Vargas [UNESP]; Colnago, Luiz Alberto; de Vasconcelos Silva, Josineudson Augusto II [UNESP]; Mercadante, Maria Eugênia Zerlotti (Elsevier, 2023)
The aim of the present study was to identify and quantify the metabolites (metabolome analysis) of the pectoralis major muscle in male red-winged tinamou (Rhynchotus rufescens) selected for growth traits. A selection index was developed for females [body weight (BW), chest circumference (CC), and thigh circumference (TC)] and males [BW, CC, TC, semen volume, and sperm concentration] in order to divide the animals into 2 experimental groups: selection group with a higher index (TinamouS) and commercial group with a lower index (TinamouC). Twenty male offspring of the 2 groups (TinamouS, n = 10; TinamouC, n = 10) were confined for 350 d. The birds were slaughtered and pectoralis major muscle samples were collected, subjected to polar and apolar metabolites extractions and analyzed by proton nuclear magnetic resonance (1H NMR) spectroscopy. Analysis of the polar metabolomic profile identified 65 metabolites; 29 of them were differentially expressed between the experimental groups (P < 0.05). The TinamouS groups exhibited significantly higher concentrations (P < 0.05) of 25 metabolites, including anserine, aspartate, betaine, carnosine, creatine, glutamate, threonine, 3-methylhistidine, NAD+, pyruvate, and taurine. Significantly higher concentrations of cysteine, beta-alanine, lactose, and choline were observed in the TinamouC group (P < 0.05). The metabolites identified in the muscle provided information about the main metabolic pathways (higher impact value and P < 0.05), for example, phenylalanine, tyrosine and tryptophan biosynthesis; alanine, aspartate and glutamate metabolism; D-glutamine and D-glutamate metabolism; β-alanine metabolism; glycine, serine and threonine metabolism; taurine and hypotaurine metabolism; histidine metabolism; phenylalanine metabolism. The NMR spectra of apolar fraction showed 8 classes of chemical compounds. The metabolome analysis shows that the selection index resulted in the upregulation of polyunsaturated fatty acids, unsaturated fatty acids, phosphocholines, phosphoethanolamines, triacylglycerols, and glycerophospholipids. The present study suggests that, despite few generations, the selection based on muscle growth traits promoted changes in metabolite concentrations in red-winged tinamou.
Keywords: metabolomics; muscle growth; NMR; selection index; Tinamidae